KELAS MULTIPLE INTELLIGENCES PESANTREN MODERN DI MADURA - Iwan Kuswandi; Tri Sukitman; Jamilah Jamilah; M. Ridwan; Mas’odi Mas’odi; Jamilah (Sekolah Tinggi Pariwisata Mataram, 2020)
This study described the implementation of education in TMI Al-Amien Prenduan. It also analyzed its teacher’s role in curriculum development at the multiple intelligences class. This study is a case study. Data was collected through observation, interview and documentation and analyzed using qualitative Model. Data validation was carried out using triangulation of data, method and source. The findings showed that the education process in TMI Al-Amien Prenduan run for 24 hour per day and used Multiple Intelligences approach in dividing the class. Classes at TMI are divided into class groups, enrichment of Islamic religious lessons and enrichment of Arabic class, Indonesian language and literature class, Mathematics and natural science class, and social sciences and English enrichment class. Teachers in this institution play three important roles, namely professional educator, learning guide, and curriculum development. They are involved in the development of Master Plan for Semester Education Program. In addition, they also carry the structural responsibility as managers.